2000
DOI: 10.1021/ic000598b
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Imides:  77Se NMR Investigations of the SeCl2tBuNH2 Reaction and X-ray Structures of Se3(NtBu)3, tBuNSe(μ-NtBu)2SO2, and tBuNSe(μ-NtBu)2SeO

Abstract: The reaction of SeCl2 with tert-butylamine in various molar ratios in THF at -78 degrees C has been investigated by 77Se NMR spectroscopy. In addition to the known Se-N heterocycles Se6(NtBu)2 (1) and Se9(NtBu)6 (2), the acyclic imidoselenium(II) dichlorides ClSe[N(tBu)Se]nCl (4, n = 1; 5, n = 2) and two new cyclic selenium imides [Se3(NtBu)2]n (3, n = 1 or 2) and Se3(NtBu)3 (6) have been isolated and identified. An X-ray analysis shows that 6 is a six-membered ring in a chair conformation with magnitude of d(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 37 publications
7
79
0
Order By: Relevance
“…[34][35][36] A similar [2+2] cycloaddition has also been observed between Se(N t Bu)2 and t BuNSeO. 37 Sandblom et al 28 have reported a DFT study of the conformations and dimerization energies of E(NMe)2 (E = S, Se, Te). 38 These calculations have verified the facile [2+2] cycloaddition of Te(NMe)2.…”
Section: -32mentioning
confidence: 76%
“…[34][35][36] A similar [2+2] cycloaddition has also been observed between Se(N t Bu)2 and t BuNSeO. 37 Sandblom et al 28 have reported a DFT study of the conformations and dimerization energies of E(NMe)2 (E = S, Se, Te). 38 These calculations have verified the facile [2+2] cycloaddition of Te(NMe)2.…”
Section: -32mentioning
confidence: 76%
“…15 Herberhold and Jellen claimed the formation of "Se3(N t Bu)2" from the decomposition of 1a, 12 but subsequent studies showed that this product is Se9(N t Bu)6. 14 This new finding suggests that the smaller oligomer [Se3(N t Bu)2]n (n = 1 or 2), which was isolated from the reaction of SeCl2 with tert-butylamine in THF, 14 is also a five-membered ring (n = 1). The structure of a related five-membered ring Se3(AsPh)2 has been reported.…”
Section: Computational Detailsmentioning
confidence: 99%
“…1-3) can be compared with the experimental values 11,14 and with the molecular parameters that have been observed for monomeric sulfur 49 and selenium diimides. 11 The calculated parameters are found to be close to the experimental values, where available:…”
Section: Cyclodimerization Of Chalcogen Diimides and Related Cycloaddmentioning
confidence: 99%
See 2 more Smart Citations